Preparation method and application of manganese self-doped double-coated silicon oxide negative electrode material
Through the preparation of manganese self-doped double-coated silicon oxide negative electrode material, the problem of insufficient energy density and electrochemical performance of lithium-ion batteries is solved, and the improvement of high energy density and long cycle stability is achieved.
Patent Information
- Application Number
- CN202211053550.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-08-31
AI Technical Summary
The energy density of lithium-ion batteries is limited by the capacity of graphite anode materials, and the silicon oxide anode materials have problems with the initial Coulomb efficiency, low conductivity and volume effects, which limits their large-scale application.
The preparation method of manganese self-doped double-coated silicon oxide negative electrode material is adopted to form a high-conductive, high-density multi-carbohydrate-coated SiOx structure through hydrothermal reaction and multiple gelation processes, forming a porous network structure to enhance electricity Chemical properties.
The energy density and electrochemical performance of lithium-ion batteries are significantly improved, the first-time efficiency and cycling stability are improved, and the conductivity and capacity are enhanced by doped MnO.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries and relates to a negative electrode material, and in particular to a preparation method and application of a manganese self-doped double-coated silicon oxide negative electrode material. Background Art
[0002] Lithium-ion batteries have been widely used in many fields due to their excellent cost-effectiveness, such as mobile phones, Bluetooth headsets, hearing aids, car batteries, energy storage power stations, spacecraft, deep-sea exploration, etc., providing great convenience for life and strong support for scientific and technological development.
[0003] As one of the key components, the negative electrode directly determines the performance of lithium-ion batteries. Currently, graphite-based negative electrode materials are mainly used in the market. However, although graphite negative electrode materials have outstanding cycle life, their capacity is limited, which seriously limits the energy density of lithium-ion batteries. Therefore, finding a new type of high-capacity, safe and long-cycle material to replace graphite-based negative electrode materials has become the key to the further development of lithium-ion batteries.
[0004] Silicon is considered the most promising candidate to replace graphite because it is the second most abundant element in the earth's crust and has an ultra-high theoretical capacity (4200 mAh / g). However, the severe volume expansion of silicon during lithiation / delithiation and the high production cost of nanostructured silicon seriously hinder its further widespread application. Recent studies have found that silicon oxide is promising to replace elemental silicon because it has extremely abundant reserves, low cost and is easy to synthesize. At the same time, compared with elemental silicon, silicon oxide shows smaller volume changes during cycling, and byproducts such as lithium oxide and lithium silicate generated in situ during the first lithiation process can buffer large volume changes and improve cycle stability. Although considered as a promising candidate for the next generation of negative electrodes, silicon oxide also has the following disadvantages: (1) In the first cycle, the irreversible formation of inactive Li2O and Li4SiO4 in the solid electrolyte interphase greatly reduces the initial coulombic efficiency. In the full battery, the low initial coulombic efficiency leads to excessive lithium ion consumption in the first cycle, resulting in a significant decrease in energy density; (2) The inherent low conductivity of silicon oxide seriously reduces its electrochemical activity; (3) There is still a non-negligible volume effect in the lithiation / delithiation process.
[0005] To this end, researchers have done a lot of research on silicon oxide anode materials in recent years. These include: developing low-cost and controllable pre-lithiation technology to improve the first coulombic efficiency of silicon oxide-based anode materials; optimizing the oxygen content of silicon oxide to achieve high specific capacity, long cycle life and low voltage hysteresis; developing effective and controllable reduction methods to convert SiO2 to SiOx; better understanding the electrochemical reaction mechanism between Li and silicon oxide; exploring new binders and electrolyte additives suitable for high-capacity silicon oxide-based anode materials, etc.
[0006] However, the existing technology still has the following technical defects: the limited capacity of graphite negative electrode materials seriously restricts the further improvement of the energy density of lithium-ion batteries, and silicon oxides still have problems such as low initial coulombic efficiency, low electrical conductivity, and volume effect during use, which restricts large-scale applications. Summary of the invention
[0007] The present invention provides a manganese self-doped double-coated silicon oxide negative electrode material, and applies the negative electrode material to a lithium ion battery, the energy density and electrochemical performance of the battery core are significantly improved, thereby overcoming the defects of the prior art.
[0008] To achieve the above object, the present invention provides a method for preparing a manganese self-doped double-coated silicon oxide negative electrode material, which has the following characteristics: using reduced graphene oxide as a skeleton, a heavy carbon hydrogel is prepared by hydrothermal reaction, and during the gelation process, SiOx that has been pre-compounded with a titanium source is coated therein; then, on the basis of the heavy carbon hydrogel, carbon oxide tubes are repeatedly introduced for gelation, and manganese is doped during the gelation process; through repeated cycles of the gelation process, a new gel is in-situ grown on the old gel, and Mn 2+ The carbon aerogel is then coated on the SiOx surface by a manganese-doped high-conductivity, high-density multi-carbon hydrogel-coated SiOx structure after coordination reaction with the carboxyl groups on the gel to form a ring-shaped chelate. The manganese-doped high-conductivity, high-density multi-carbon hydrogel-coated SiOx structure is then obtained. After freeze-drying, activation, and calcination, the blocky multi-carbon aerogel is coated on the SiOx surface to form a manganese self-doped double-coated silicon oxide negative electrode material with a porous network structure.
[0009] Furthermore, the present invention provides a method for preparing a manganese self-doped double-coated silicon oxide negative electrode material, which may also have the following characteristics:
[0010] S1. Dissolve tetrabutyl titanate in ethanol, stir evenly, add SiOx and continue stirring until the ethanol evaporates completely, then calcine in an inert atmosphere to obtain titanium silicate composite SiO, recorded as TiSiO4@SiO;
[0011] S2, mixing graphite oxide and a reducing agent, dispersing them in deionized water, and heating the mixture to form a dispersion A; adding the TiSiO4@SiO obtained in S1 to the dispersion A under continuous heating and rapid stirring, and adding a high molecular compound containing a carbonyl group, stirring the mixture evenly, and then performing a hydrothermal reaction to form a CG / TiSiO4@SiO hydrogel; after cooling the mixture to room temperature, freeze-drying the CG / TiSiO4@SiO hydrogel to obtain a single layer of CG / TiSiO4@SiO aerogel;
[0012] S3, dissolving the Mn-containing compound in a deionized water-ethanol mixed solution, stirring to obtain solution B; mixing the oxidized carbon tubes and the reducing agent, dispersing them in deionized water, to obtain solution C; adding solution C to solution B, and continuing to stir until the mixture is uniform;
[0013] S4, puncturing the surface of the CG / TiSiO4@SiO aerogel prepared in S2, and then transferring it to the mixed solution obtained in S3 for immersion; then performing a hydrothermal reaction to form a Mn-doped double CG / TiSiO4@SiO hydrogel; after cooling to room temperature, freeze-drying the Mn-doped double CG / TiSiO4@SiO hydrogel to obtain a Mn-doped double CG / TiSiO4@SiO aerogel, recorded as 2-MnO / CG / TiSiO4@SiO aerogel;
[0014] S5, repeat S3 and S4 n times until the Mn-doped n-fold CG / TiSiO4@SiO aerogel achieves the desired effect, recorded as n-MnO / CG / TiSiO4@SiO aerogel;
[0015] S6, soaking the n-MnO / CG / TiSiO4@SiO aerogel obtained in S5 in an activator solution for etching and activation, then washing it thoroughly with ethanol and drying it;
[0016] S7. Thermally reduce the product obtained in S6 in an inert atmosphere to prepare a finished product of a manganese self-doped double-coated silicon oxide negative electrode material.
[0017] Furthermore, the present invention provides a method for preparing a manganese self-doped double-coated silicon oxide negative electrode material, which may also have the following characteristics: wherein, in S1, the SiOx, 0<x≤2; the mass ratio of tetrabutyl titanate to SiOx is (0.01~1):1; the calcination temperature is 600℃~1200℃, and the calcination temperature is 1h~10h.
[0018] Furthermore, the present invention provides a method for preparing a manganese self-doped double-coated silicon oxide negative electrode material, which may also have the following characteristics: wherein, in S2, the graphite oxide is prepared by any method; the reducing agent is one of ascorbic acid, sodium borohydride, sodium sulfide, hydrazine hydrate and other reducing inorganic or organic compounds, or any mixture; the graphite oxide and the reducing agent are dispersed in deionized water by ultrasound, and the ultrasonic dispersion time is 1h~3h; the viscosity of the dispersion A ranges from 100 mPa.s to 10000. mPa.s; during the heating reaction and continuous heating, the heating temperature is 50°C~100°C, the heating reaction time is 30min~5h, and the stirring time of continuous heating is 10min; the mass ratio of graphite oxide, reducing agent, and TiSiO4@SiO is 1:(1~3):(1~5), and after adding TiSiO4@SiO to dispersion A, the mass proportion of mixed solid is 0.1%~20%; the polymer compound containing carbonyl group is one or more of ketone, aldehyde, and carboxylic acid polymers, specifically but not limited to polyvinyl pyrrolidone (PVP), polyacrylic acid (PAA), polyacrylamide (PAM), polymethoxy acetal (PMAC); the mass ratio of the polymer compound containing carbonyl group to TiSiO4@SiO is (1~8):1; the temperature of the hydrothermal reaction is 110°C~200°C, and the time of the hydrothermal reaction is 2h~10h.
[0019] Furthermore, the present invention provides a method for preparing a manganese self-doped double-coated silicon oxide negative electrode material, which may also have the following characteristics: wherein, in S3, the Mn-containing compound is a mixture of one or more of inorganic manganese salts MnSO4, Mn(CH3COO)2, Mn(NO3)2, and MnCl2; the Mn-containing compound is dissolved in a deionized water-ethanol mixed solution and stirred for 15 minutes; the oxidized carbon tubes are a mixture of one or more of oxidized single-walled carbon nanotubes, oxidized single-walled carbon microtubes, oxidized multi-walled carbon nanotubes, and oxidized multi-walled carbon microtubes; the reducing agent is one of ascorbic acid, sodium borohydride, sodium sulfide, hydrazine hydrate and other reducing inorganic or organic compounds, or any mixture thereof; the mass ratio of the oxidized carbon tubes to the reducing agent is 1: (1~3), and in solution C, the mass proportion of the mixed solid is 0.05%~20%; the amount ratio of manganese salt to solution C is 1 mol: (1~100) g.
[0020] Furthermore, the present invention provides a method for preparing a manganese self-doped double-coated silicon oxide negative electrode material, which may also have the following characteristics: wherein, in S4, a steel needle with a diameter of 0.01 mm is used to puncture the surface of the CG / TiSiO4@SiO aerogel, and the punctured surface includes one of the top, bottom, and side surfaces or any mixed surface; the temperature of the hydrothermal reaction is 110°C~200°C, and the time of the hydrothermal reaction is 2h~10h.
[0021] Furthermore, the present invention provides a method for preparing a manganese self-doped double-coated silicon 2 Oxide negative electrode material, which may also have the following characteristics: wherein, in S5, n≥2.
[0022] Furthermore, the present invention provides a method for preparing a manganese self-doped double-coated silicon oxide negative electrode material, which may also have the following characteristics: wherein, in S6, the activator is a mixture of one or more of KOH, HF, KMnO4, NaOH, and H3PO4; the concentration of the activator solution is 0.5 M~1.5 M, and the activation time is 10h~40h.
[0023] Furthermore, the present invention provides a method for preparing a manganese self-doped double-coated silicon oxide negative electrode material, which may also have the following characteristics: wherein, in S7, the inert atmosphere is an inert pure gas or an inert mixed gas, the thermal reduction temperature is 300°C~600°C, and the thermal reduction time is 1h~8h.
[0024] The present invention also provides an application of the manganese self-doped double-coated silicon oxide negative electrode material prepared by the above preparation method, which has the following characteristics: a lithium ion battery is prepared by using the manganese self-doped double-coated silicon oxide negative electrode material, and the preparation method comprises the following steps:
[0025] Step 1, preparation of positive electrode sheet: adding the positive electrode active material, conductive agent and binder dry powder to a homogenizing tank, adding them to dry, then adding a dispersion medium, continuing to stir, to obtain a viscous positive electrode slurry; or dispersing the binder separately into the dispersion medium, mixing evenly, and then mixing and stirring with the positive electrode active material and the conductive agent to obtain a viscous positive electrode slurry; evenly coating the viscous positive electrode slurry on the aluminum foil current collector, drying, rolling, cutting, welding the pole ears, and preparing a positive electrode sheet; preferably, the positive electrode active material is a mixture of one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate, and the dispersion medium is N-methylpyrrolidone or deionized water;
[0026] Step 2, preparation of negative electrode sheet: the negative electrode active material, the manganese self-doped double-coated silicon oxide negative electrode material, the conductive agent, and the thickener dry powder are mixed and added to a homogenizing tank for drying, and then a dispersion medium is added, stirring is continued, and finally a binder is added, and the mixture is stirred evenly to obtain a viscous negative electrode slurry; or the thickener is dispersed in the dispersion medium alone, mixed evenly, and then mixed and stirred with the negative electrode active material, the manganese self-doped double-coated silicon oxide negative electrode material, and the conductive agent, and finally a binder is added, and the mixture is stirred evenly to obtain a viscous negative electrode slurry; the viscous negative electrode slurry is evenly coated on the copper foil current collector, dried, rolled, cut, and welded to the pole ears to prepare a negative electrode sheet; wherein the mass percentage of the manganese self-doped double-coated silicon oxide negative electrode material in the total dry powder slurry is ≥0 wt%, ≤60wt%; preferably, the negative electrode active material is one or a mixture of two or more of natural graphite, artificial graphite, soft carbon, and hard carbon, and the dispersion medium is deionized water or N-methylpyrrolidone;
[0027] Step 3: Lithium-ion battery assembly: Alternately place the positive electrode sheet prepared in step 1, the negative electrode sheet prepared in step 2 and the separator, wind them into an electrode group, load them into a battery shell, encapsulate, inject liquid, age at high temperature, pressurize and form, and divide the capacity to prepare a lithium-ion battery.
[0028] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a manganese self-doped double-coated silicon oxide negative electrode material, using reduced graphene oxide as a skeleton, adopting hydrothermal reaction, and coating SiOx sintered with a titanium source in advance during its gelation process. During the process, the abundant carbonyl oxygen in the polymer is respectively connected with the H atoms on the surface of TiSiO4@SiO particles and the H atoms in the surface functional groups (hydroxyl, carboxyl) of the reduced graphene oxide sheet through hydrogen bonds, and a single hydrogel is formed through a self-assembly process in the solution; then, on the basis of the single carbon hydrogel, a small amount of oxidized carbon tubes are repeatedly introduced, and manganese is doped at the same time; after freeze drying, activation, and calcination, the polymer becomes amorphous carbon coated on the SiO surface, and the block shape of the outer ring of tight carbon aerogel is retained, and is also tightly coated on the SiO surface, and a manganese-doped high-conductivity, high-density multi-carbon aerogel coated SiO composite material is successfully prepared. The negative electrode material is applied to lithium ion batteries to prepare high energy density lithium ion batteries.
[0029] After extensive research and repeated experiments, it was found that the manganese self-doped double-coated silicon oxide negative electrode material prepared by the present invention has a porous network structure with excellent conductivity. The double coating layer effectively reduces the contact area between silicon oxide and the electrolyte, significantly improving the initial efficiency; and the coating layer can act as a buffer layer to alleviate the volume expansion of silicon oxide during the cycle, thereby improving the cycle stability. In addition, the doped MnO can not only inhibit the accumulation of oxidized carbon tubes and improve conductivity, but also contribute nearly twice the capacity of graphite.
[0030] Specifically, through repeated cycles of the gelation process, new gel grows in situ on the old gel, and Mn 2+ The carbon aerogel reacts with the carboxyl groups on the gel to form a ring-shaped chelate. This method can obtain a SiOx structure with high conductivity and high density doped with manganese. After freeze drying, activation and calcination, the block shape of the carbon aerogel is retained and tightly coated on the SiOx surface to form a composite material with a porous network structure. The multiple carbon aerogels make the composite material have good conductivity, and the three-dimensional network coating layer effectively reduces the contact area between silicon oxide and electrolyte, and can promote the transmission of electrolyte ions; at the same time, during the calcination process, the titanium source on the SiOx surface can react with the silicon dioxide produced by disproportionation at high temperature to generate titanium silicate, which is coated on the surface of silicon oxide, effectively reducing the consumption of lithium ions in the first cycle of the whole battery and significantly improving the first efficiency. In addition, the coating layer is electrochemically inert and stable, and can be used as a buffer layer to alleviate the volume expansion of silicon oxide during the cycle process, thereby improving the cycle stability; in addition, the nucleophilicity of manganese salt ions has an important influence on the microstructure of porous 3D carbon aerogel. MnO appears as a beaded nano-skeleton microstructure on the carbon aerogel, which inhibits the accumulation of oxidized carbon tubes, which can not only further improve the conductivity of the composite material and facilitate rapid electron transmission, but also MnO can contribute nearly twice the capacity of graphite due to its own characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a photo of the preparation process of a heavy CG / TiSiO4@SiO hydrogel in Example 1;
[0032] Figure 2 is a schematic diagram of preparing the composite material in Example 1;
[0033] Figure 3 This is the principle diagram of how TiSiO4@SiO can effectively reduce the first-cycle lithium ion consumption in the full battery compared to pure SiO;
[0034] Figure 4 It is a comparison chart of 1.2C / 0.7C cycle curves of Example 1 and comparative example battery cells at 45°C. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with specific embodiments.
[0036] The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The "room temperature" and "normal pressure" mentioned in the present invention refer to the temperature and pressure during daily operation, which are generally 25°C and one atmosphere.
[0037] The battery designed in the following embodiments and comparative examples is a 385677 soft-pack lithium-ion battery.
[0038] Example 1
[0039] This embodiment provides a manganese self-doped double-coated silicon oxide negative electrode material, and the preparation method thereof comprises the following steps:
[0040] S1. Dissolve 0.06 mol of tetrabutyl titanate in 200 ml of ethanol, stir evenly, add 50 g of SiO and continue stirring until the ethanol evaporates completely, then transfer to a tube furnace and calcine at 900 °C for 6 h in an inert atmosphere to obtain titanium silicate composite SiO, recorded as TiSiO4@SiO;
[0041] S2, 10g of graphite oxide and 20g of ascorbic acid were mixed, ultrasonically dispersed in 600ml of deionized water, and heated in a water bath at 80°C. After about 40min, the mixed solution gradually became viscous, and when the viscosity was about 1000 mPa.s, dispersion A was obtained; at this time, the TiSiO4@SiO obtained in S1 was added thereto, and 260g of PVP was added at the same time, and the mixture was stirred for 10min, and then transferred to a hydrothermal reactor for hydrothermal reaction at 150°C for 5h to form a CG / TiSiO4@SiO hydrogel; after cooling to room temperature, the CG / TiSiO4@SiO hydrogel was placed in a freeze dryer for freeze drying to obtain a single layer of CG / TiSiO4@SiO aerogel;
[0042] S3, dissolving 1 mol of Mn(NO3)2 in a deionized water-ethanol mixed solution, and magnetically stirring for 15 min to obtain solution B; mixing 7 g of carbon oxide tubes and 10 g of ascorbic acid, and ultrasonically dispersing them in deionized water to obtain solution C; adding solution C to solution B, and continuing to stir until the mixture is uniform;
[0043] S4, using a high-quality steel needle (Φ = 0.01 mm) to pierce the surface of the CG / TiSiO4@SiO aerogel prepared in S2, and then transferring it to the mixed solution obtained in S3 and immersing it for 10 minutes; then transferring it to a hydrothermal reactor, and hydrothermally reacting at 150°C for 5 hours to form a Mn-doped double CG / TiSiO4@SiO hydrogel; after cooling to room temperature, the Mn-doped double CG / TiSiO4@SiO hydrogel was placed in a freeze dryer for freeze drying to obtain a Mn-doped double CG / TiSiO4@SiO aerogel, recorded as 2-MnO / CG / TiSiO4@SiO aerogel;
[0044] S5, repeat the gelation step for 7 times, and the product is recorded as 7-MnO / CG / TiSiO4@SiO aerogel;
[0045] S6, soaking the 7-MnO / CG / TiSiO4@SiO aerogel obtained in S5 in 1.2 M phosphoric acid for 24 h, and then washing and drying with ethanol;
[0046] S7. Place the product obtained in S6 in a tubular furnace and perform thermal reduction at 400° C. for 4 h in an inert atmosphere to obtain a finished product of a manganese self-doped double-coated silicon oxide negative electrode material.
[0047] The button cell prepared by using the material of this example has an initial lithium insertion capacity of 1360 mAh / g, an initial charge and discharge efficiency of 81.5%, and a capacity retention rate of 89.4% after 150 cycles.
[0048] The material of this embodiment is mixed with graphite to prepare a full battery, and the preparation method includes the following steps:
[0049] Step 1: Preparation of positive electrode sheet: Mix the positive electrode active material nickel-cobalt-manganese ternary, Ketjen black and binder PVDF dry powder in a mass ratio of 98.3:0.7:1 and add them to a homogenization tank for drying, then add the dispersion medium NMP to make the solid content at 70%-85%, continue stirring to obtain a viscous positive electrode slurry; evenly coat the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut and weld the pole ears to prepare the positive electrode sheet;
[0050] Step 2, preparation of negative electrode sheet: the thickener CMC is dispersed separately in the dispersion medium deionized water and stirred evenly, the negative electrode active material artificial graphite, the material of this embodiment and carbon black are added together into a homogenization tank and dried evenly, and then the dispersion medium deionized water and the pre-dispersed thickener CMC are added in sequence, and the solid content is adjusted to 45%-55%, and stirring is continued. Finally, the binder SBR is added and stirred evenly to obtain a viscous negative electrode slurry; wherein the mass ratio of artificial graphite, the material of this embodiment, carbon black, thickener CMC and binder SBR is 70:20:6:2:2, and finally the viscous negative electrode slurry is evenly coated on the copper foil current collector, dried, rolled, cut, and welded to the pole ears to prepare the negative electrode sheet;
[0051] Step 3: Lithium-ion battery assembly: The positive electrode sheet prepared in step 1, the negative electrode sheet prepared in step 2 and the separator are wound into an electrode group in a certain manner, and loaded into a battery shell (formed by aluminum-plastic packaging film), packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery.
[0052] Example 2
[0053] This embodiment provides a manganese self-doped double-coated silicon oxide negative electrode material, and the preparation method thereof comprises the following steps:
[0054] S1. Dissolve 0.05 mol of tetrabutyl titanate in 200 ml of ethanol, stir evenly, add 50 g of SiO2 and continue stirring until the ethanol evaporates completely. Then transfer the mixture to a tube furnace and calcine it at 800 °C for 6 h in an inert atmosphere to obtain titanium silicate composite SiO2, which is recorded as TiSiO4@SiO2.
[0055] S2, 10g of graphite oxide and 20g of ascorbic acid were mixed, ultrasonically dispersed in 600ml of deionized water, heated in a water bath at 80℃, and the mixed solution gradually became viscous after about 40min. When the viscosity was about 1000mPa.s, dispersion A was obtained; at this time, the TiSiO4@SiO obtained in S1 was added thereto, and 240g of PVP was added at the same time, and the mixture was stirred for 10min, and then transferred to a hydrothermal reactor for hydrothermal reaction at 180℃ for 5h to form CG / TiSiO4@SiO hydrogel; after cooling to room temperature, the CG / TiSiO4@SiO hydrogel was placed in a freeze dryer for freeze drying to obtain a layer of CG / TiSiO4@SiO aerogel;
[0056] S3, dissolving 1.2 mol Mn(NO3)2 in a deionized water-ethanol mixed solution, and magnetically stirring for 15 min to obtain solution B; mixing 7 g of carbon oxide tubes and 10 g of ascorbic acid, and ultrasonically dispersing them in deionized water to obtain solution C; adding solution C to solution B, and continuing to stir until the mixture is uniform;
[0057] S4, using a high-quality steel needle (Φ = 0.01 mm) to pierce the surface of the CG / TiSiO4@SiO aerogel prepared in S2, and then transferring it to the mixed solution obtained in S3 and immersing it for 10 minutes; then transferring it to a hydrothermal reactor, and hydrothermally reacting at 180°C for 5 hours to form a Mn-doped double CG / TiSiO4@SiO hydrogel; after cooling to room temperature, the Mn-doped double CG / TiSiO4@SiO hydrogel was placed in a freeze dryer for freeze drying to obtain a Mn-doped double CG / TiSiO4@SiO aerogel, which was recorded as 2-MnO / CG / TiSiO4@SiO aerogel;
[0058] S5, repeat the gelation step for 5 times, and the product is recorded as 5-MnO / CG / TiSiO4@SiO aerogel;
[0059] S6, soaking the 5-MnO / CG / TiSiO4@SiO aerogel obtained in S5 in 1.2 M phosphoric acid for 24 h, and then washing and drying with ethanol;
[0060] S7. Place the product obtained in S6 in a tubular furnace and perform thermal reduction at 400° C. for 4 h in an inert atmosphere to obtain a finished product of a manganese self-doped double-coated silicon oxide negative electrode material.
[0061] The button cell prepared by using the material of this example had an initial lithium insertion capacity of 1355 mAh / g, an initial charge and discharge efficiency of 80.2%, and a capacity retention rate of 88.6% after 150 cycles.
[0062] The material of this embodiment is mixed with graphite to prepare a full battery, and the preparation method includes the following steps:
[0063] Step 1: Preparation of positive electrode sheet: Mix the positive electrode active material nickel-cobalt-manganese ternary, Ketjen black and binder PVDF dry powder in a mass ratio of 98.3:0.7:1 and add them to a homogenization tank for drying, then add the dispersion medium NMP to make the solid content at 70%-85%, continue stirring to obtain a viscous positive electrode slurry; evenly coat the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut and weld the pole ears to prepare the positive electrode sheet;
[0064] Step 2, preparation of negative electrode sheet: the thickener CMC is dispersed separately in the dispersion medium deionized water and stirred evenly, the negative electrode active material artificial graphite, the material of this embodiment and carbon black are added together into a homogenization tank and dried evenly, and then the dispersion medium deionized water and the pre-dispersed thickener CMC are added in sequence, and the solid content is adjusted to 45%-55%, and stirring is continued. Finally, the binder SBR is added and stirred evenly to obtain a viscous negative electrode slurry; wherein the mass ratio of artificial graphite, the material of this embodiment, carbon black, thickener CMC and binder SBR is 74:16:6:2:2, and finally the viscous negative electrode slurry is evenly coated on the copper foil current collector, dried, rolled, cut, and welded to the pole ears to prepare the negative electrode sheet;
[0065] Step 3: Lithium-ion battery assembly: The positive electrode sheet prepared in step 1, the negative electrode sheet prepared in step 2 and the separator are wound into an electrode group in a certain manner, and loaded into a battery shell (formed by aluminum-plastic packaging film), packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery.
[0066] Example 3
[0067] This embodiment provides a manganese self-doped double-coated silicon oxide negative electrode material, and the preparation method thereof comprises the following steps:
[0068] S1. Dissolve 0.06 mol of tetrabutyl titanate in 200 ml of ethanol, stir evenly, add 50 g of SiO2 and continue stirring until the ethanol evaporates completely. Then transfer the mixture to a tube furnace and calcine it at 800 °C for 4 h in an inert atmosphere to obtain titanium silicate composite SiO2, which is recorded as TiSiO4@SiO2.
[0069] S2, 10g of graphite oxide and 20g of ascorbic acid were mixed, ultrasonically dispersed in 600ml of deionized water, and heated in a water bath at 80°C. After about 40min, the mixed solution gradually became viscous, and when the viscosity was about 1000 mPa.s, dispersion A was obtained; at this time, the TiSiO4@SiO obtained in S1 was added thereto, and 240g of PAA was added at the same time, and the mixture was stirred for 10min, and then transferred to a hydrothermal reactor for hydrothermal reaction at 150°C for 5h to form a CG / TiSiO4@SiO hydrogel; after cooling to room temperature, the CG / TiSiO4@SiO hydrogel was placed in a freeze dryer for freeze drying to obtain a single layer of CG / TiSiO4@SiO aerogel;
[0070] S3, dissolving 2 mol Mn(CH3COO)2 in a deionized water-ethanol mixed solution, and magnetically stirring for 15 min to obtain solution B; mixing 5 g carbon oxide tubes and 10 g ascorbic acid, and ultrasonically dispersing them in deionized water to obtain solution C; adding solution C to solution B, and continuing to stir until the mixture is uniform;
[0071] S4, using a high-quality steel needle (Φ = 0.01 mm) to pierce the surface of the CG / TiSiO4@SiO aerogel prepared in S2, and then transferring it to the mixed solution obtained in S3 and immersing it for 10 minutes; then transferring it to a hydrothermal reactor, and hydrothermally reacting at 150°C for 5 hours to form a Mn-doped double CG / TiSiO4@SiO hydrogel; after cooling to room temperature, the Mn-doped double CG / TiSiO4@SiO hydrogel was placed in a freeze dryer for freeze drying to obtain a Mn-doped double CG / TiSiO4@SiO aerogel, recorded as 2-MnO / CG / TiSiO4@SiO aerogel;
[0072] S5, repeat the gelation step 6 times in total, and the product is recorded as 6-MnO / CG / TiSiO4@SiO aerogel;
[0073] S6, soaking the 6-MnO / CG / TiSiO4@SiO aerogel obtained in S5 in 1.2 M phosphoric acid for 24 h, and then washing and drying with ethanol;
[0074] S7. Place the product obtained in S6 in a tube furnace and perform thermal reduction at 400° C. for 5 h in an inert atmosphere to obtain a finished product of a manganese self-doped double-coated silicon oxide negative electrode material.
[0075] The button cell was prepared using the material of this example, and the initial lithium insertion capacity was 1357 mAh / g, the initial charge and discharge efficiency was 81.0%, and the capacity retention rate after 150 cycles was 88.1%.
[0076] The material of this embodiment is mixed with graphite to prepare a full battery, and the preparation method includes the following steps:
[0077] Step 1: Preparation of positive electrode sheet: Mix the positive electrode active material nickel-cobalt-manganese ternary, Ketjen black and binder PVDF dry powder in a mass ratio of 98.3:0.7:1 and add them to a homogenization tank for drying, then add the dispersion medium NMP to make the solid content at 70%-85%, continue stirring to obtain a viscous positive electrode slurry; evenly coat the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut and weld the pole ears to prepare the positive electrode sheet;
[0078] Step 2, preparation of negative electrode sheet: the thickener CMC is dispersed separately in the dispersion medium deionized water and stirred evenly, the negative electrode active material artificial graphite, the material of this embodiment and carbon black are added together into a homogenization tank and dried evenly, and then the dispersion medium deionized water and the pre-dispersed thickener CMC are added in sequence, and the solid content is adjusted to 45%-55%, and stirring is continued. Finally, the binder SBR is added and stirred evenly to obtain a viscous negative electrode slurry; wherein the mass ratio of artificial graphite, the material of this embodiment, carbon black, thickener CMC and binder SBR is 76:14:6:2:2, and finally the viscous negative electrode slurry is evenly coated on the copper foil current collector, dried, rolled, cut, and welded to the pole ears to prepare the negative electrode sheet;
[0079] Step 3: Lithium-ion battery assembly: The positive electrode sheet prepared in step 1, the negative electrode sheet prepared in step 2 and the separator are wound into an electrode group in a certain manner, and loaded into a battery shell (formed by aluminum-plastic packaging film), packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery.
[0080] Example 4
[0081] This embodiment provides a manganese self-doped double-coated silicon oxide negative electrode material, and the preparation method thereof comprises the following steps:
[0082] S1. Dissolve 0.03 mol of tetrabutyl titanate in 200 ml of ethanol, stir evenly, add 50 g of SiO2, and continue stirring until the ethanol evaporates completely. Then transfer the mixture to a tube furnace and calcine at 900 °C for 6 h in an inert atmosphere to obtain titanium silicate composite SiO2, which is recorded as TiSiO4@SiO2.
[0083] S2, 10g of graphite oxide and 20g of ascorbic acid were mixed, ultrasonically dispersed in 600ml of deionized water, and heated in a water bath at 80°C. After about 40min, the mixed solution gradually became viscous, and when the viscosity was about 1000 mPa.s, dispersion A was obtained; at this time, the TiSiO4@SiO obtained in S1 was added thereto, and 195g of PAA was added at the same time, and the mixture was stirred for 10min, and then transferred to a hydrothermal reactor for hydrothermal reaction at 150°C for 5h to form a CG / TiSiO4@SiO hydrogel; after cooling to room temperature, the CG / TiSiO4@SiO hydrogel was placed in a freeze dryer for freeze drying to obtain a single layer of CG / TiSiO4@SiO aerogel;
[0084] S3, dissolving 2.5 mol Mn(CH3COO)2 in a deionized water-ethanol mixed solution, and magnetically stirring for 15 min to obtain solution B; mixing 5 g carbon oxide tubes and 10 g ascorbic acid, and ultrasonically dispersing them in deionized water to obtain solution C; adding solution C to solution B, and continuing to stir until the mixture is uniform;
[0085] S4, using a high-quality steel needle (Φ = 0.01 mm) to pierce the surface of the CG / TiSiO4@SiO aerogel prepared in S2, and then transferring it to the mixed solution obtained in S3 and immersing it for 10 minutes; then transferring it to a hydrothermal reactor, and hydrothermally reacting at 150°C for 5 hours to form a Mn-doped double CG / TiSiO4@SiO hydrogel; after cooling to room temperature, the Mn-doped double CG / TiSiO4@SiO hydrogel was placed in a freeze dryer for freeze drying to obtain a Mn-doped double CG / TiSiO4@SiO aerogel, recorded as 2-MnO / CG / TiSiO4@SiO aerogel;
[0086] S5, repeat the gelation step for 5 times, and the product is recorded as 5-MnO / CG / TiSiO4@SiO aerogel;
[0087] S6, soaking the 5-MnO / CG / TiSiO4@SiO aerogel obtained in S5 in 1.2 M phosphoric acid for 24 h, and then washing and drying with ethanol;
[0088] S7. Place the product obtained in S6 in a tubular furnace and perform thermal reduction at 400° C. for 4 h in an inert atmosphere to obtain a finished product of a manganese self-doped double-coated silicon oxide negative electrode material.
[0089] The button cell prepared by using the material of this example has an initial lithium insertion capacity of 1353 mAh / g, an initial charge and discharge efficiency of 79.5%, and a capacity retention rate of 88.4% after 150 cycles.
[0090] The material of this embodiment is mixed with graphite to prepare a full battery, and the preparation method includes the following steps:
[0091] Step 1: Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, Ketjen black and binder PVDF dry powder in a mass ratio of 98.3:0.7:1 and add them to a homogenization tank for drying, then add the dispersion medium NMP to make the solid content at 70%-85%, continue stirring to obtain a viscous positive electrode slurry; evenly coat the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut and weld the pole ears to prepare the positive electrode sheet;
[0092] Step 2, preparation of negative electrode sheet: the thickener CMC is dispersed separately in the dispersion medium deionized water and stirred evenly, the negative electrode active material artificial graphite, the material of this embodiment and carbon black are added together into a homogenization tank and dried evenly, and then the dispersion medium deionized water and the pre-dispersed thickener CMC are added in sequence, and the solid content is adjusted to 45%-55%, and stirring is continued. Finally, the binder SBR is added and stirred evenly to obtain a viscous negative electrode slurry; wherein the mass ratio of artificial graphite, the material of this embodiment, carbon black, thickener CMC and binder SBR is 79:11:6:2:2, and finally the viscous negative electrode slurry is evenly coated on the copper foil current collector, dried, rolled, cut, and welded to the pole ears to prepare the negative electrode sheet;
[0093] Step 3: Lithium-ion battery assembly: The positive electrode sheet prepared in step 1, the negative electrode sheet prepared in step 2 and the separator are wound into an electrode group in a certain manner, and loaded into a battery shell (formed by aluminum-plastic packaging film), packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery.
[0094] Comparative Example
[0095] The battery design process, raw materials, and production steps adopted in this comparative example are basically the same as those in Example 1, with the only difference being that the negative electrode slurry in this comparative example does not use the manganese self-doped double-coated silicon oxide negative electrode material prepared by the present invention, but uses a simple raw material silicon oxide. The positive electrode slurry formula is an active material of lithium cobalt oxide, Ketjen black, and a binder PVDF, and the mass ratio of lithium cobalt oxide, Ketjen black, and binder PVDF is 98.3:0.7:1. The negative electrode slurry formula is an active material of artificial graphite, raw materials of silicon oxide, carbon black, thickener CMC, and binder SBR, and the mass ratio of artificial graphite, raw materials of silicon oxide, carbon black, thickener CMC, and binder SBR is 70:20:6:2:2.
[0096] The initial capacity and room temperature cycle of the battery cells prepared in Examples 1 to 4 were compared with those in the comparative example. The results are shown in Table 1.
[0097] Table 1 Initial capacity and parameters after room temperature cycling of batteries prepared in various embodiments and comparative examples
[0098]
[0099] The 1.2C / 0.7C cycle curves of the cells prepared in Example 1 and the comparative example at 45°C were tested and plotted. The results are as follows: Figure 4 shown.
[0100] From Table 1 and Figure 4 The data show that the high energy density battery designed using the manganese self-doped double-coated silicon oxide negative electrode material prepared by the present invention has good long-term cycle performance.
[0101] The above are only some preferred embodiments of the present invention and do not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiments still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a manganese self-doped double-coated silicon oxide negative electrode material, Features: Using reduced graphene oxide as the skeleton, a heavy carbon hydrogel is prepared by hydrothermal reaction, and during the gelation process, SiOx that has been pre-compounded with a titanium source is coated therein; The method of compounding SiOx with titanium source is as follows: tetrabutyl titanate is dissolved in ethanol, stirred evenly, SiOx is added and stirred continuously until the ethanol evaporates completely, and then calcined in an inert atmosphere to obtain titanium silicate composite SiO, which is recorded as TiSiO 4 @SiO; Then, on the basis of a heavy carbon hydrogel, oxidized carbon tubes were repeatedly introduced for gelation, and manganese was doped during the gelation process; through repeated cycles of the gelation process, new gels grew in situ on the old gels, and Mn 2+ The carboxyl groups on the gel undergo coordination reactions to form a ring-shaped chelate, resulting in a manganese-doped high-conductivity, high-density multi-carbon hydrogel-coated SiOx structure; Then, after freeze drying, activation and calcination, the blocky multi-carbon aerogel is coated on the SiOx surface to form a manganese self-doped double-coated silicon oxide negative electrode material with a porous network structure.
2. The method for preparing the manganese self-doped double-coated silicon oxide negative electrode material according to claim 1, Features: The specific steps include: S1. Dissolve tetrabutyl titanate in ethanol, stir evenly, add SiOx and continue stirring until the ethanol evaporates completely, then calcine in an inert atmosphere to obtain titanium silicate composite SiO, denoted as TiSiO 4 @SiO; S2, mixing graphite oxide and a reducing agent, dispersing them in deionized water, heating them to react and forming a dispersion A; while continuously heating and stirring, mixing the TiSiO 4 @SiO is added to dispersion A, and a high molecular compound containing a carbonyl group is added at the same time. After stirring evenly, a hydrothermal reaction is carried out to form CG / TiSiO 4 @SiO hydrogel; after cooling to room temperature, CG / TiSiO 4 @SiO hydrogel was freeze-dried to obtain a layer of CG / TiSiO 4 @SiO aerogel; S3, dissolving the Mn-containing compound in a deionized water-ethanol mixed solution, stirring to obtain solution B; mixing the oxidized carbon tubes and the reducing agent, dispersing them in deionized water, to obtain solution C; adding solution C to solution B, and continuing to stir until the mixture is uniform; S4, CG / TiSiO prepared in S2 4 The surface of the @SiO aerogel was punctured and then transferred to the mixed solution obtained by S3 for immersion; then a hydrothermal reaction was performed to form a Mn-doped dual CG / TiSiO 4 @SiO hydrogel; after cooling to room temperature, the Mn-doped dual CG / TiSiO 4 @SiO hydrogel was freeze-dried to obtain Mn-doped dual CG / TiSiO 4 @SiO aerogel, denoted as 2-MnO / CG / TiSiO 4 @SiO aerogel; S5, repeat S3 and S4 n times until the Mn-doped n-fold CG / TiSiO 4 @SiO aerogel achieves the desired effect, recorded as n-MnO / CG / TiSiO 4 @SiO aerogel; S6, the n-MnO / CG / TiSiO obtained in S5 4 @SiO aerogel is soaked in activator solution, etched, activated, washed, and dried; S7. Thermally reduce the product obtained in S6 in an inert atmosphere to prepare a finished product of a manganese self-doped double-coated silicon oxide negative electrode material.
3. The method for preparing the manganese self-doped double-coated silicon oxide negative electrode material according to claim 2, characterized in that: in, In S1, the SiOx, 0<x≤2; The calcination temperature is 600°C~1200°C, and the calcination temperature is 1h~10h.
4. The method for preparing the manganese self-doped double-coated silicon oxide negative electrode material according to claim 2, characterized in that: in, In S2, the graphite oxide and the reducing agent are dispersed in deionized water by ultrasound, and the ultrasonic dispersion time is 1h~3h; The viscosity of the dispersion A ranges from 100 mPa.s to 10000 mPa.s; During the heating reaction and continuous heating, the heating temperature is 50°C to 100°C, the heating reaction time is 30min to 5h, and the stirring time of continuous heating is 10min; The graphite oxide, reducing agent, TiSiO 4 The mass ratio of TiSiO is 1: (1-3): (1-5), and TiSiO is added to dispersion A. 4 @SiO, the mass proportion of mixed solids is 0.1%~20%; The carbonyl-containing polymer compound is one or more of ketone, aldehyde, and carboxylic acid polymers; the carbonyl-containing polymer compound and TiSiO 4 @The mass ratio of SiO is (1~8):1; The temperature of the hydrothermal reaction is 110° C. to 200° C., and the time of the hydrothermal reaction is 2 h to 10 h.
5. The method for preparing the manganese self-doped double-coated silicon oxide negative electrode material according to claim 2, characterized in that: in, In S3, the Mn-containing compound is an inorganic manganese salt MnSO 4 、Mn(CH 3 COO 2 、Mn(NO 3 ) 2 、MnCl 2 A mixture of one or more of the following; The Mn-containing compound was dissolved in the deionized water-ethanol mixed solution and stirred for 15 min; The oxidized carbon tubes are a mixture of one or more of oxidized single-walled carbon nanotubes, oxidized single-walled carbon microtubes, oxidized multi-walled carbon nanotubes, and oxidized multi-walled carbon microtubes; The mass ratio of the oxidized carbon tube to the reducing agent is 1: (1-3), the mass proportion of the mixed solid in solution C is 0.05%-20%; the dosage ratio of the manganese salt to solution C is 1 mol: (1-100) g.
6. The method for preparing the manganese self-doped double-coated silicon oxide negative electrode material according to claim 2, characterized in that: in, In S4, a steel needle with a diameter of 0.01 mm was used to 4 @Punch holes on the surface of SiO aerogel; The temperature of the hydrothermal reaction is 110° C. to 200° C., and the time of the hydrothermal reaction is 2 h to 10 h.
7. The method for preparing the manganese self-doped double-coated silicon oxide negative electrode material according to claim 2, characterized in that: in, In S5, n≥2.
8. The method for preparing the manganese self-doped double-coated silicon oxide negative electrode material according to claim 2, characterized in that: in, In S6, the activator is KOH, HF, KMnO 4 , NaOH, H 3 PO 4 A mixture of one or more of the following; The concentration of the activator solution is 0.5 M to 1.5 M, and the activation time is 10 h to 40 h.
9. The method for preparing the manganese self-doped double-coated silicon oxide negative electrode material according to claim 2, characterized in that: in, In S7, the thermal reduction temperature is 300°C~600°C, and the thermal reduction time is 1h~8h.
10. Application of the manganese self-doped double-coated silicon oxide negative electrode material obtained by the preparation method according to any one of claims 1 to 9, Features: The manganese self-doped double-coated silicon oxide negative electrode material is used to prepare a lithium ion battery, and the preparation method comprises the following steps: Step 1: Preparation of positive electrode sheet: Mix the positive electrode active material, conductive agent and binder dry powder and add them to a homogenizing tank for drying, then add the dispersion medium and continue stirring to obtain a viscous positive electrode slurry; or disperse the binder separately into the dispersion medium, mix well and then mix and stir with the positive electrode active material and conductive agent to obtain a viscous positive electrode slurry; evenly apply the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut and weld the pole ears to prepare the positive electrode sheet; Step 2, preparation of negative electrode sheet: the negative electrode active material, the manganese self-doped double-coated silicon oxide negative electrode material, the conductive agent, and the thickener dry powder are mixed and added to a homogenizing tank for drying, and then a dispersion medium is added, and stirring is continued, and finally a binder is added, and the mixture is stirred evenly to obtain a viscous negative electrode slurry; or the thickener is dispersed in the dispersion medium alone, mixed evenly, and then mixed and stirred with the negative electrode active material, the manganese self-doped double-coated silicon oxide negative electrode material and the conductive agent, and finally a binder is added, and the mixture is stirred evenly to obtain a viscous negative electrode slurry; the viscous negative electrode slurry is evenly coated on the copper foil current collector, dried, rolled, cut, and welded to the ear to prepare a negative electrode sheet; wherein the mass percentage of the manganese self-doped double-coated silicon oxide negative electrode material in the total dry powder slurry is ≥0 wt%, ≤60wt%; Step 3: Lithium-ion battery assembly: Alternately place the positive electrode sheet prepared in step 1, the negative electrode sheet prepared in step 2 and the separator, wind them into an electrode group, load them into a battery shell, encapsulate, inject liquid, age at high temperature, pressurize and form, and divide the capacity to prepare a lithium-ion battery.
